2014
DOI: 10.5012/bkcs.2014.35.11.3261
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical Water Splitting on a Delafossite CuGaO2Semiconductor Electrode

Abstract: A pellet of polycrystalline CuGaO 2 with a delafossite structure was prepared from Ga 2 O 3 and CuO by hightemperature solid-state synthesis. The CuGaO 2 pellet was a p-type semiconductor for which the electrical conductivity, carrier density, carrier mobility and Seebeck coefficient were 5.34 × 10 s −1 at room temperature, and +360 µV/K, respectively. It also exhibited two optical transitions at about 2.7 and 3.6 eV. The photoelectrochemical properties of the CuGaO 2 pellet electrode were investigated in aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The CuGaO 2 material has shown favorable attributes in terms of its ability to catalyze overall water-splitting of adsorbed H 2 O, meaning that its band edges are likely to be located at suitable energies in order to satisfy the conditions for H 2 O redox potential. However, Lee et al [38] also describe reduced photocatalytic activity below UV wavelengths (hν < 3.2 eV), in spite of the fact that CuGaO 2 having also shown weaker absorption edges around 2.7 eV in separate studies [37].…”
Section: Introductionmentioning
confidence: 98%
“…The CuGaO 2 material has shown favorable attributes in terms of its ability to catalyze overall water-splitting of adsorbed H 2 O, meaning that its band edges are likely to be located at suitable energies in order to satisfy the conditions for H 2 O redox potential. However, Lee et al [38] also describe reduced photocatalytic activity below UV wavelengths (hν < 3.2 eV), in spite of the fact that CuGaO 2 having also shown weaker absorption edges around 2.7 eV in separate studies [37].…”
Section: Introductionmentioning
confidence: 98%
“…However, Cu + -based delafossite oxides (CuMO 2 , M = Fe, Co, Cr, Al, etc. ) provide an alternative to solve the stability issue, while maintaining the optoelectronic properties suitable for PEC, making them promising photocathode materials. Among the delafossite oxides, CuFeO 2 is considered as the most appealing material because of its suitable band gap for visible light absorption, high stability, and earth-abundant elements. Furthermore, it has been reported that CuFeO 2 shows ferroelectric properties, which may provide a favorable internal electric field for fast separation and transport of photoexcited carriers. Besides, CuFeO 2 has also been demonstrated to reduce CO 2 to formate under illumination, and the conversion efficiency of CuFeO 2 reaches the maximum at −0.9 V saturated calomel electrode .…”
Section: Introductionmentioning
confidence: 99%
“…Wide‐bandgap delafossite materials have also been examined for PEC water splitting. Besides CuGaO 2 , [ 128 ] Díaz‐García et al [ 129 ] inspected the photoelectrochemical properties of CuCrO 2 delafossite thin films prepared by a sol gel route. Although the material bandgap is too wide to absorb in the visible range (3.15 eV) of the solar spectrum, the IPCE attained values near 6% at 350 nm, which is remarkably high compared with other p‐type oxide materials.…”
Section: Ternary Oxides As Photocathodesmentioning
confidence: 99%